(untitled) - Gastel, Barbara (Santa Barbara, California, 2016)
In addition to the information on writing for scientific journals, this book provides additional advice for the scientist of the 21st century: - What ethical issues are important in scientific publishing? - What should a scientist know about rights and permissions? - How does a scientist write a grant proposal, or prepare progress reports for administrators? - What should a scientist know to work well with the media, or to write for a general audience? All of this practical information makes How to Write and Publish a Scientific Paper the essential guide that scientists need for succeeding in the competitive environment of today.
Viết bài báo xuất bản và trình bày kết quả nghiên cứu (Write a scientific paper for publication and present research results),Nguyên lý giảng dạy tiếng Anh
Keywords: Technical writing,Kỹ thuật viết